Economic System in India - Gayatri Sunkad (Research Parks Publishers, 2022)
Economic system in India is surrounded by primary sector, secondary sector and service sector. Our economic system in India is influenced by mainly agriculture and allied activities. Our economic system was influenced by the social and spiritual point of view that was ‘’ Sarve Janah Sukhino Bhavantu’’. Our economic system in India was influenced by the socialism, as well as mixed economic system. But even though, it was dominated by agriculture, animal husbandry, allied activities and still the much importance is given to production and manufacturing industries. Now in the modern era, our economic system is influenced by science, technology internet, media and communication. Now due to emergence of globalization, privatization, liberalization, the world is becoming to small global village. The economic system in India is heavily depends upon social system because it also depend upon the life style of the people. The economic system also influences the life style of the people.